Electric Quadrupole E2- Transitions of 170-174 Yb Isotopes - M. Abu El Sheikh, Mohd Kh. M; Okhunov, Abdurahim; Usmanov, Ph N.; Hassan, Torla (Institute of Physics Publishing, 2018)
The non-adiabatic effects which is manifested in the electric properties of low-lying states of even-even deformed nuclei are studied. A simple phenomenological model which takes into account the Coriolis mixing of Kπ = 0+ n , 2+ n and Kπ = 1+ ν state bands. The Calculations for isotopes 170−174Y b, are carried out. The reduced probability of electric quadrupole transitions from the states 0+ ν and 2+ ν - bands to the ground (gr) state band is calculated and non adiabatic effect is discussed. The ratio of E2– transitions RIK from 0+ 2 , 0+ 3 , 2+ 1 , and 2+ 2 bands are calculated and compared with the experimental data